Neural crest and sons: role of neural crest cells and Schwann cell precursors in development and gland embryogenesis - Knyazeva, Aleksandra; Dyachuk, Vyacheslav (Frontiers in Cell and Developmental Biology, 2024)
In this review, we consider the multipotency of neural crest cells (NCCs), Schwann cell precursors (SCPs), and their role in embryogenesis base on genetic tracing and knock out model animals and single cell transcriptomic analysis. In particular, we summarize and analyze data on the contribution of NCCs and SCPs to the gland development and functions.